Social justice issues and racism in the college classroom perspectives from different voices - Davis, Dannielle Joy, 1974-; Boyer, Patricia G. (Bingley, U.K. : Emerald, 2013)
The focus of Social Justice Issues and Racism in the College Classroom is faculty and students of color at postsecondary institutions and the racial challenges they encounter in college classrooms. To achieve this aim, the book highlights the voices of various racial/ethnic groups of faculty and students, including international scholars. Additionally, the book will inform and bring attention to non-minority faculty and students of social justice issues related to race in the classroom and offer suggestions on how to be supportive of people of color. Several frameworks will be utilized in this book to assist readers in better understanding ideas, concepts, and practices. Specifically, a social justice framework, critical race theory, and White privilege are used to better explore the featured topics. Both quantitative and qualitative (e.g., auto-ethnographic, interviews, etc.) data are utilized throughout the book to give voice to the authors. Questions posed for this edited book are as follows: How do faculty members include social justice issues related to race/ethnicity in their curricula? How are issues associated with race or ethnicity discussed in the classroom by students, as well as minority and nonminority faculty? What are the experiences of students of color in the classroom working with faculty of different races and ethnicities? Overall the book provides information to assist students and faculty of color with survival skills in complex environments.
Teaching for social justice through embracing identity tensions / Christine W. Nganga -- Teaching race, pushing back, and making meaningful change / Marybeth Gasman -- Advocating for change : a reflection on my journey to social justice education / Bonita K. Butner -- Confessions of a border-crossing brotha-scholar / Ty-Ron M.O. Douglas -- The experiences of marginalized academics and understanding the majority : implications for institutional policy and practice / Dannielle Joy Davis -- Chicanos teaching social justice in higher education/chicanos enseñando justicia social en la universidad : experiences at predominately white and hispanic serving institutions / Juan Carlos González, Edwardo L. Portillos -- Revolutionary reforestation and white privilege in a critical race doctoral program / Amy A. Hunter, Matthew D. Davis -- Research as activism / Linda Sue Warner -- Reflective journaling in a college multicultural education classroom : looking past, present, and future / Eunyoung Kim -- Classroom experiences through the lens of social justice : the postsecondary experiences of three black female students / Katrina M. Hubbard, Annette M. Burris, Ashley L. Gray -- The experience of conducting a study of racial or ethnic dynamics : voices of doctoral students in colleges of education / Aimee Howley ... [et al.] -- Perspective of a majority student / Kathleen M. Kanz-White -- Reflections on a critical race theory project with educational leaders / Abul Pitre.
Includes index.
Print version record
Keywords: Education -- Inclusive Education; Education -- Multicultural Education; Inclusive education -- Mainstreaming; Higher & further education, tertiary education; Discrimination in education; Education, Higher